(untitled) (Linguostylistic Studies, 2020)
The article considers the peculiarities of the nation stereotype functioning in the novel Notes of a Ukrainian Madman by Lina Kostenko. In the focus of the analysis are the basic concepts (the nation, the people, Ukrainians, the state, a society), by means of which the author’s stereotype of the Ukrainian nation is revealed. A set of evaluative nominations that construct a model of the nation stereotype has been established. The greatest number of epithets refers to the lexeme nation. They create a nominative field of the author’s stereotype and express mostly negative connotations. The study has revealed that the expression of the author’s model of the stereotype is the image of the protagonist as a representative of the society of the Ukrainians, living in the XX-XXI centuries, whose communicative behavior demonstrates an evaluative attitude to his people. Evaluative nominations that construct a model of national stereotype in the text of the novel are mostly endowed with negative connotations and high expressiveness. The usage features of various linguistic and stylistic means, metaphorical techniques, as well as occasionalisms, loanwords, ethnonymes in the author’s representation of the Ukrainian nation are analyzed. Verbalization of the image of Ukraine is carried out by means of syntactic constructions of monologue, dialogue, and quotation. The factors that could influence the individual perception and reproduction of the nation stereotype in the literary text are identified. The author’s stereotype in the analyzed work appears not idealized, but, due to the individual experience of the writer, social and political factors, critically considered. Prospects for further research on national stereotypes in linguistics concern the development of the criteria for selecting factual material, texts of various functional styles and genres, as well as the comparative study of the specifics of modeling stereotypes, their verbalization and dynamics in the works of different writersю